Pemberian Inokulum Fungi Mikoriza Arbuskula (Fma) Campuran terhadap Kemunculan Penyakit Busuk Pangkal Batang Sclerotium pada Tanaman Cabai Rawit dan Cabai Merah - Wira Dhyaksa Pradana; Uki Dwiputranto; Juni Safitri Muljowati (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Cayenne pepper (Capsicum frutescens) and red chili (Capsicum annuum), including vegetables and fruit are widely consumed by the public, and also have many benefits. At present, the market demand for cayenne pepper and red chili is very high, so equalization must be made from the production sector. The conventional way of handling such as the administration of pesticides or other chemicals is less effective because it causes side effects that have a large enough impact, so an alternative technique is used that is to use Arbuscular Mycorrhizal Fungi (FMA) thus, research on the administration of Arbuscular Mycorrhoid Fungi Inoculum is thus carried out. (FMA) Mixture of Sclerotium Stem Rot Rotation in Capsicum frutescens and Capsicum annuum. The purpose of this study was to determine the effect of mixed FMA inoculums in suppressing the intensity of sclerotium stem rot rot disease in cayenne pepper (Capsicum frutescens) and red chili peppers (Capsicum annuum) and to determine the optimal dose of mixed AMF in suppressing the intensity of sclerotium stem rot rot on cayenne plants (Capsicum frutescens) and red chili plants (Capsicum annuum). This study used a Completely Randomized Design (CRD) with different doses of mixed AMF inoculums (0, 10, 15, 20, 25 g FMA with zeolite / plant carrier medium). The results of this study indicate that the treatment of mixed AMF inoculums on the intensity of sclerotium stem rot disease in cayenne and red chili plants can reduce the intensity of Sclerotium stem rot disease by 22% and in red chili plants by 11%.